Estudo do clima urbano em cidade de pequeno porte : o caso de Nobres-MT - Lorençoni, Ana Maria Branco (2024)
Cities can be regarded as one of the most intense social interventions in nature, however it is essential to analyze the environmental changes that occur due to urban planning processes that are inappropriate to the characteristics of the environments in which cities are built. Alterations in the urban environment resulting from the accelerated process of urbanization in recent decades demand attention, with climate being a critical dimension of nature subject to changes that directly impact people's lives, with the potential to generate anything from a loss of quality of life to health issues. Thus, this dissertation aims to verify the existence of a specific urban climate for the city of Nobres-MT by analyzing the influence of environmental elements and social actions on the local climate. The investigation focuses primarily on the thermal field, specifically Channel I: thermal comfort, the thermodynamic subsystem of the Urban Climate System proposed by Monteiro, 1976. To analyze the city's urban climate, temperature and humidity data were recorded from a representative period of the dry season and another for the region's rainy season, through fixed points spread across the urban area of the municipality and the mobile transect technique, which covered areas covering the rural surroundings, peripheral and central regions of the city. At the end of the studies, it was found that despite Nobres being a small municipality, there is the formation of heat islands, and the importance of preserving green areas was verified, and the need for public authorities to monitor and establish the Municipal Master Plan.